A Review of Analysis and Existing Simulation Model of Three Phase Permanent Magnet Synchronous Motor Drive (PMSM) - Ali Khan, Md. Yakub (Control Systems and Optimization Letters, 2024)
The main objective of this research is to review the existing simulation model of three phase Permanent Magnet Synchronous Motor Drive (PMSM). This review enhances the understanding of dynamic and steady-state performance of PMSM system. Because of their exceptional power density, precise control features, and great efficiency, permanent magnet synchronous motors, or PMSMs, have drawn a lot of interest. A thorough examination of the modeling, simulation, and control approaches for three-phase PMSM drives is given in this paper. To comprehend motor dynamics, the research looks at a number of mathematical models of PMSM, such as analogous circuit models and d-q axis representation. Software tools such as MATLAB/Simulink are used in simulation techniques to test these models and forecast system performance under various operating situations. In addition, the impact of control systems like Direct Torque Control (DTC) and Field-Oriented Control (FOC) on performance optimization is explored. The research gaps that still need to be filled are highlighted in the paper's conclusion, along with possible future study topics. The review emphasizes how well-advanced control techniques like Direct Torque Control (DTC) and Field-Oriented Control (FOC) can improve PMSM performance. It also stresses how crucial precise d-q axis modeling and simulation tools are to reducing torque ripple, increasing efficiency, and guaranteeing reliable operation in a variety of applications.